(untitled) - Holgate, Stephen T. (Philadelphia, 2001)
In the second edition, we took note of the feedback of many clinicians who asked us if we could put primary emphasis on the clinical manifestations of allergy and augment this with a solid scientific background. This we have attempted to do starting with an entirely new chapter on the principles of allergy diagnosis, a skill which is crucial to all practicing physicians. This is followed by a series of chapters focusing on the histopathology, diagnosis and management of allergic disease in individual organs.
Keywords: Allergy,Hypersensitivity,Dị ứng,Mẫn cảm